2023
DOI: 10.1186/s13000-023-01300-4
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive immunohistochemical analysis of IMP2 and IMP3 in 542 cases of ovarian tumors

Abstract: Background IMP2 and IMP3 are mRNA binding proteins involved in carcinogenesis. We examined a large cohort of ovarian tumors with the aim to assess the value of IMP2 and IMP3 for differential diagnosis, and to assess their prognostic significance. Methods Immunohistochemical analyses with antibodies against IMP2 and IMP3 were performed on 554 primary ovarian tumors including 114 high grade serous carcinomas, 100 low grade serous carcinomas, 124 clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…This study supports the existing understanding that LGSC and HGSC are distinct types of tumors. They differ in their origins, pathogenesis, morphology, molecular characteristics, prognostic factors, and response to treatment, as outlined in previous research [53]. Our research revealed that LGSCs possess a smaller quantity of Ki67 + cells, aligning with their documented slow progression rate, especially when compared to HGSCs.…”
Section: Discussionsupporting
confidence: 74%
“…This study supports the existing understanding that LGSC and HGSC are distinct types of tumors. They differ in their origins, pathogenesis, morphology, molecular characteristics, prognostic factors, and response to treatment, as outlined in previous research [53]. Our research revealed that LGSCs possess a smaller quantity of Ki67 + cells, aligning with their documented slow progression rate, especially when compared to HGSCs.…”
Section: Discussionsupporting
confidence: 74%
“…The scoring was performed by a trained pathologist with Slidescore [26]. The expression of p16 was regarded as block positive (diffuse staining of tumor cells in the nuclear and/or cytoplasmatic compartment) or negative (focal/patchy or absent staining) [27]. Three staining patterns were recorded: absent, heterogeneous and block.…”
Section: Immunohistochemistry Stainingmentioning
confidence: 99%